Predation of the giant Miocene caiman Purussaurus on a mylodontid ground sloth in the wetlands of proto-Amazonia - Pujos, François Roger Francis (2020)
Thirteen million years ago in South America, the Pebas Mega-Wetland System sheltered multi-taxon crocodylian assemblages, with the giant caiman Purussaurus as the top predator. In these Miocene swamps where reptiles and mammals coexisted, evidence of their agonistic interactions is extremely rare. Here, we report a tibia of the mylodontid sloth Pseudoprepotherium bearing 46 predation tooth marks. The combination of round and bisected, shallow pits and large punctures that collapsed extensive portions of cortical bone points to a young or sub-adult Purussaurus (approx. 4 m in total length) as the perpetrator. Other known crocodylians of the Pebas Systemwere either too small at adulthood or had discordant feeding anatomy to be considered. The pattern of tooth marks suggests that the perpetrator attacked and captured the ground sloth from the lower hind limb, yet an attempt of dismembering cannot be ruled out. This discovery from the Peruvian Amazonia provides an unusual snapshot of the dietary preferences of Purussaurus andreveals that prior to reaching its giant size, young individuals might have fed upon terrestrial mammals of about the size of a capybara.